Resistance in adapting to sustainable mobility and new Sustainable Mobility Indicator – case study of a Polish agglomeration - Matusiewicz, Maria (Prace Komisji Geografii Komunikacji PTG, 2020)
Sustainable growth is now the foundation of economic growth, especially if the 2020 pandemic prompts the conclusion that the over-exploitation of planet’s goods is ultimately turning against humanity. Despite the climate crisis, Poles are reluctant to give up cars, and city authorities in Poland do not increase the quality and efficiency of public transport. Young people around the world are seen as hope for changing trends. The aim of the article is to verify the hypothesis about greater awareness of young people in Poland about climate change, manifested by mobility habits, compared to the older generation. The hypothesis was verified by a study onducted on a group of 67 students commuting to the university at the age of 21-23 and a group of 45 commuters aged 25-65. The Sustainable Mobility Indicator (SMI) was created for the purposes of the article. The SMI considers daily travels of residents of a large Polish city. With the use of the created indicator, the hypothesis was rejected.